Dehydration of mango (Mangifera indica) puree by vacuum oven drying - Maristela, Evangeline C.; Gatchalian, Miflora M. (1972.)
ABSTRACT The study hoped to develop mango puree into powder using the vacuum oven method. The variables in the study were the initial soluble solids content (S.S.) of the puree in terms of Brix (14B, 30B and 50B) and the temperature of dehydration (100F, 130F and 160F). The main purpose of such variations was to determine the optimum dehydration conditions as they affect the powdered products' characteristics. The procedure involved the pureeing of the mangoes; adjusting to the desired S.S.; feeding into the vacuum oven, maintaining a vacuum of 27 to 28 inches Hg and at the required temperature. Dehydration was continued until the samples were dry enough to be scraped as flakes. They were further dried in a dessicator to a stage that grinding of the samples into powder was permissible. Both objective and sensory results indicated that the best powders were obtained at a temperature of 130F and 160F with an initial concentration of 30B. Although the powders had brownish-yellow color, much of the mango odor and flavor were preserved even upon reconstitution.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mango puree; Mango, Dried